1999
DOI: 10.1021/jp9926847
|View full text |Cite
|
Sign up to set email alerts
|

Radiolysis of Polyethylene Films Containing Arenes:  Bromopyrene Dissociation and Pyrene Binding in Polymer Films

Abstract: Radiation induced dehalogenation of haloarenes and binding of arenes have been studied in polyolefin films. Dehalogenation takes place from a highly excited triplet state that is formed by the recombination of arene radical ions, while binding takes place through a polymer aryl radical intermediate. The latter process is dependent on the reactivity of the polymer radical and decreases in low molecular weight and branched polymer films. It is found that energy deposited by high-energy irradiation is transferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Pulse radiolysis studies of polymers containing arene probes have shown a rapid formation of the arene ionic components very shortly after the end of the pulse. 16,17 Therefore, in polyethylene, adding styrene groups in the polymer backbone would lead to charge transfers to the benzene rings, very close to the observation of K. Okamoto 18 during pulse radiolysis study of polystyrene in cyclohexane.…”
Section: Introductionsupporting
confidence: 62%
“…Pulse radiolysis studies of polymers containing arene probes have shown a rapid formation of the arene ionic components very shortly after the end of the pulse. 16,17 Therefore, in polyethylene, adding styrene groups in the polymer backbone would lead to charge transfers to the benzene rings, very close to the observation of K. Okamoto 18 during pulse radiolysis study of polystyrene in cyclohexane.…”
Section: Introductionsupporting
confidence: 62%
“…Diffusion of small molecules has been employed previously to explore the microstructures of several polymer types, 9a, including polyethylenes, 10a-d, but not UHMWPE . To measure in-diffusion rates and calculate the related diffusion constants ( D ), 10a-e,g,h Py - UHMWPE-h ν films were immobilized and immersed in N 2 -saturated 0.95 M DMA /MeOH solutions at constant temperature while the decrease in the intensity of their pyrenyl fluorescence was monitored as a function of time (Table and Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The microstructure of UHMWPE has been probed by ESR, solid-state 13 C NMR, Raman spectroscopy, and, especially, X-ray diffraction . Others and we have employed photophysical methods to investigate local morphological changes in polymer films, including other types of polyethylene. However, to the best of our knowledge, UHMWPE has not been investigated in this way.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the initial deposition of energy by ionizing radiation like X-rays creates local concentrations of high energy (i.e., single ionization spurs) within an alkane medium (Spinks and Woods 1964). Within spurs, processes such as electron ejection leads to hole formation and the generation of stable pyrene radical cations and anions which, upon recombination with electrons, form pyrene excited states (Biscoglio andThomas 2000, Szadkowska-Nicze et al 1992). The predominant processes within the spurs are C-H and C-C bond scissions that lead to the formation of lower molecular weight alkanes (Zagórski 2002) in addition to the attachment processes mentioned here.…”
Section: Resultsmentioning
confidence: 99%